Basic English Book 1 - Kaur, Harbans (University Press Plc, 2009)
This book contain the basic rules and essential information for mastering the English language. This series will be an excellent English language guide not only for primary students but also for those who wish to conquer the language effectively and efficiently for everyday use...
Keywords: Juvenile Non-Fiction; Language-English language